Ear Mite Removal in the Santa Catalina Island Fox (Urocyon littoralis catalinae): Controlling Risk Factors for Cancer Development - Moriarty, Megan E.; Vickers, T. Winston; Clifford, Deana L.; Garcelon, David K.; Gaffney, Patricia M.; Lee, Kenneth W.; King, Julie L.; Duncan, Calvin L.; Boyce, Walter M. (PLOS ONE, 2015)
Ear mites (Otodectes cynotis) and ear canal tumors are highly prevalent among federally endangered Island foxes (Urocyon littoralis catalinae) living on Santa Catalina Island off the coast of Southern California. Since studies began in the 1990s, nearly all foxes examined were found to be infected with ear mites, and ceruminous gland tumors (carcinomas and adenomas) were detected in approximately half of all foxes ≥ 4 years of age. We hypothesized that reduction of ear mite infection would reduce otitis externa and ceruminous gland hyperplasia, a risk factor for tumor development. In this study, we conducted a randomized field trial to assess the impact of acaricide treatment on ear mite prevalence and intensity of infection, otitis externa, ceruminous gland hyperplasia, and mite-specific IgG and IgE antibody levels. Treatment was highly effective at eliminating mites and reducing otitis externa and ceruminous gland hyperplasia, and mite-specific IgG antibody levels were significantly lower among uninfected foxes. Ceruminous gland hyperplasia increased in the chronically infected, untreated foxes during the six month study. Our results provide compelling evidence that acaricide treatment is an effective means of reducing ear mites, and that mite removal in turn reduces ear lesions and mite-specific IgG antibody levels in Santa Catalina Island foxes. This study has advanced our understanding of the underlying pathogenesis which results in ceruminous gland tumors, and has helped inform management decisions that impact species conservation.